How do people with MND and caregivers experience a digital mental health intervention? A qualitative study - Pinto, Cathryn; Geraghty, Adam W. A.; Pagnini, Francesco; Yardley, Lucy; Dennison, Laura (Frontiers in Psychiatry, 2023)
Objective We urgently need to develop and evaluate more psychological interventions to support people with Motor Neurone Disease (MND) and caregivers. We used the person-based approach to develop a digital mental health intervention and conducted two studies to explore people’s experiences of using it. Methods In Study 1, we conducted think-aloud interviews with 9 people with MND and 8 caregivers, and used findings to refine the intervention. In Study 2, 18 people with MND and 9 caregivers used the intervention for 6 weeks after which in-depth interviews were conducted. Data from both studies were combined and analysed using thematic analysis. Results We developed 3 main themes around intervention acceptability, engagement, and usefulness. Participants highlighted the importance of accessibility and realistic presentation of information and support. Tailoring and timing intervention use to suit own needs, preferences, and disease stage was also important. Participants used the strategies presented to develop a positive outlook and regain some control. They also faced some challenges using these strategies in the context of dealing with progressive loss. Conclusion People with MND and caregivers can find digital mental health interventions useful. Intervention accessibility and flexibility are important for developing acceptable and engaging interventions for MND.